Evaluation of Ruthenium(II) N-Heterocyclic Carbene Complexes as Antibacterial Agents and Inhibitors of Bacterial Thioredoxin Reductase - Hilke Burmeister; Pascal Dietze; Lutz Preu; Julia E. Bandow; Ingo Ott (Molecules, 2021)
A series of ruthenium(II) complexes with N-heterocyclic carbene (NHC) ligands of the general type (arene)(NHC)Ru(II)X2 (where X = halide) was prepared, characterized, and evaluated as antibacterial agents in comparison to the respective metal free benzimidazolium cations. The ruthenium(II) NHC complexes generally triggered stronger bacterial growth inhibition than the metal free benzimidazolium cations. The effects were much stronger against Gram-positive bacteria (Bacillus subtilis and Staphylococcus aureus) than against Gram-negative bacteria (Escherichia coli, Acinetobacter baumannii, Pseudomonas aeruginosa), and all complexes were inactive against the fungus Candida albicans. Moderate inhibition of bacterial thioredoxin reductase was confirmed for selected complexes, indicating that inhibition of this enzyme might be a contributing factor to the antibacterial effects.